Updating the Presence of Bevelled Rim Bowls in Northern Central Zagros. Some Preliminary Data from Tepe Qaleh Naneh (Kurdistan) - Binandeh, Ali; Di Paolo, Silvana (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2023)
The cooperative project between the Bu-Ali Sina University, Hamedan (hereafter BASU) and the Institute of Heritage Science–CNR (hereafter CNR) studies the dynamics of the development of the first communities in northern central Zagros, an area that was for a long time neglected in archaeological research. The site of Tepe Qaleh Naneh is located in the Marivan plain, which has roughly at its centre Lake Zaribar, and extends to the west, south and east of the city of Marivan, c. 130 km west of Sanandaj, the capital of the Iranian Kurdistan province. The first excavations revealed a multi-layered site, dating from at least the Chalcolithic to the Islamic periods, although the Chalcolithic is probably the longest and the most important phase. The presence of Bevelled Rim Bowls (hereafter BRBs) in contexts of the mid 4th millennium BC at Qaleh Naneh requires further study. Nevertheless, their discovery in several other sites in northern central Zagros offers data on their distribution and socio-cultural significance.